O impacto da fenilcetonúria e seu tratamento dietético na qualidade de vida dos pacientes e seus cuidadores - MARÇAL, Adriano de Figueiredo (2023)
Phenylketonuria (PKU) is a rare autosomal recessive disease, characterized by a deficiency of the enzyme phenylalanine hydroxylase, without cure, where its only and most effective treatment is through a very restricted diet and free of phenylalanine. In order to assess the quality of life of PKU patients, a specific questionnaire (PKUQoL) was used. The study included 5 adolescents, 3 adults, 4 children and 10 parents who answered 40 to 65 questions. The answers obtained were linearized, in order to obtain values that ranged from 0 to 100% of impact, according to each type of question asked. The questionnaire answered by the parents indicated that the diet followed by the children is not considered a problem, they are attentive to the signs and symptoms that the disease can manifest and that they feel guilty when their children do not follow the diet correctly. Children experience most symptoms associated with the disease, feel heightened anxiety about blood tests, and are not ashamed to use metabolic formula. For adolescents, the results indicated that having phenyl is not considered a social problem, that they feel guilty for not following the phenyl diet and that they are tempted to eat forbidden foods. Adults reported feeling irritable and lacking in concentration, high anxiety about Phe levels during pregnancy, and guilt if they didn't consume the metabolic formula. Patients reported a negative impact on quality of life due to PKU.